The worlds of a Maasai warrior : an autobiography - Saitoti, Tepilit Ole. (Berkeley : University of California Press, 1988)
Recounts the author's traditional childhood, adolescence, and coming into manhood in Maasailand and of his education in Europe and America.
Includes bibliographical references (p. xxiii).
Booklist
Young Adult.
Young Adult
Keywords: Saitoti, Tepilit Ole, 1949-.; Saitoti, Tepilit Ole, 1949-.; Maasai (African people) -- Biography; Maasai (African people) -- Biography